2020
DOI: 10.3390/su12187559
|View full text |Cite
|
Sign up to set email alerts
|

Economic Development and Changes in Human Resource Management in a Sustainable Agricultural Sector: Recent Evidence from Brazilian Sugar–Alcohol Companies

Abstract: Economic development causes significant changes in the innovative processes of resource management. The purpose of this article is to discuss the sustainability of resource management in sugar–alcohol companies operating in the most productive areas of Brazil and to analyze the profile of the companies in the sector in terms of innovation and adherence to practices of human resource management. The methodological procedures were based on qualitative research. Data collection was directed toward the population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
(31 reference statements)
0
2
0
1
Order By: Relevance
“…The economic sustainable human resource management aims at cleaner production by trying to optimize usages of resources, decrease wastages, so as to attain sustainability (Severo, De Guimaraes, Dorion & Nodari, 2015). Studies on human resource management indicates that the effective use of the potentials of employees provides a competitive advantage to an organization (Paulo, Edson, Isabel & Valeria, 2020). Researches on economic sustainability of human resource management is also said to tilt more towards strategic management which focuses on the contributions of human resource management towards organizational outcomes based on supply of qualified/talented professionals in strategic areas of the organization's operations (Sparrow & Otaye-Ebede, 2014 cited in Paulo et al, 2020).…”
Section: Economic Human Resources Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The economic sustainable human resource management aims at cleaner production by trying to optimize usages of resources, decrease wastages, so as to attain sustainability (Severo, De Guimaraes, Dorion & Nodari, 2015). Studies on human resource management indicates that the effective use of the potentials of employees provides a competitive advantage to an organization (Paulo, Edson, Isabel & Valeria, 2020). Researches on economic sustainability of human resource management is also said to tilt more towards strategic management which focuses on the contributions of human resource management towards organizational outcomes based on supply of qualified/talented professionals in strategic areas of the organization's operations (Sparrow & Otaye-Ebede, 2014 cited in Paulo et al, 2020).…”
Section: Economic Human Resources Managementmentioning
confidence: 99%
“…The economic human resource management facet implies the ability of the organization to make profits and gain highly competitive advantage. Studies on HRM indicate that the effective use of the potential of employees provides a competitive advantage to an organization (Paulo et al, 2020). Karlshaus (2020), in their qualitative study on implementing part-time leadership as instrument for sustainable HR management, carried out a meta-analysis of existing studies, and found that part-time leadership model can aid the fulfilment of selected sustainable improvement goals.…”
Section: Part Time Employment and Sustainable Humanmentioning
confidence: 99%
“…With human capital becoming the central focus for organizations, companies started to compete to retain and hire valuable employees using strategic human resources policies [4]. This aspect has shifted the power towards valuable employees that can demand better contractual terms or find it elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of organizational productivity is quite enormous and challenging. According to Mourao, Kubo, Santos, and Mazucato (2020) the exigencies and complexities in reaching organizational productivity set goals have been constrained by many factors inhibiting effective productivity. These ranges from corporate underutilization of installed capacities in the manufacturing sector, arising from infrastructural deficits in Nigeria, multiplicity of tax obligations, inadequate supply of electricity to power installed plant and equipment to full capacities (Ortega & Fernando, 2019;.…”
Section: Introductionmentioning
confidence: 99%